1998
DOI: 10.1177/174182679800500506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on the Prevalence of Insulin Resistance-Associated Cardiovascular Risk Factors Among Finnish Men in Military Service

Abstract: Background Obesity, central obesity, hypertension, dyslipidemia and hyperinsulinemia tend to cluster in the same individuals as a metabolic syndrome; smoking has an adverse effect on insulin resistance. The aim of our study was to examine the occurrence of clusters of insulin-resistanceassociated abnormalities and the effect of smoking on this clustering in young men.Methods In 1995 we invited all the 1268 servicemen attending military service in the Ostrobothnian Brigade, Finland, for screening of the metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Current smoking is a significant independent risk factor for the MetS in both women and men [7,31,39,40]. In other studies, the significant association between MetS and smoking has not been observed [24,28,30].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Current smoking is a significant independent risk factor for the MetS in both women and men [7,31,39,40]. In other studies, the significant association between MetS and smoking has not been observed [24,28,30].…”
Section: Discussionmentioning
confidence: 98%
“…Cigarette smoking may also cause high blood pressure by increasing sympathetic activity, and it may elevate triglyceride levels [43]. The clustering of metabolic abnormalities associated with insulin resistance has been shown to be sixfold higher in smokers than in non-smokers [40]. However, this releationship has not been clarified, and reports on this issue are also scarce.…”
Section: Discussionmentioning
confidence: 98%
“…Smoking is known to impair insulin action and may lead to insulin resistance [51]. The inverse relationship between cigarette smoking and weight is also well documented [23].…”
Section: Discussionmentioning
confidence: 98%
“…This occurs across the lifespan, and a higher incidence of cardiovascular risk linked to insulin resistance was observed in young male smokers compared with nonsmokers (49). Both obesity and cigarette smoking are also important risk factors in many age-related diseases, accelerating the aging process via increasing oxidative stress and inflammation (51).…”
Section: Discussionmentioning
confidence: 99%